2012
DOI: 10.3329/jbsp.v7i1.11153
|View full text |Cite
|
Sign up to set email alerts
|

Power Spectral Analysis of Heart Rate Variability in Female Rheumatoid Arthritis Patients

Abstract: Background: Association of increased cardiovascular morbidity and higher sympathetic activity in patients with Rheumatoid arthritis (RA) has been recognized. Heart rate variability (HRV) is a useful measure to assess sympatho-vagal balance. Objective: To assess autonomic nerve function status in patients with Rheumatoid Arthritis (RA) by HRV analysis. Methods: This cross sectional study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka from Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…6,[11][12] The results of the present study suggests attenuated cardiac vagal modulation in Rheumatoid arthritis and the above mentioned factors may be the consequence of inflammatory process of Rheumatoid arthritis. This finding is well correlated with those published in our previous report 23 …”
Section: Discussionsupporting
confidence: 83%
“…6,[11][12] The results of the present study suggests attenuated cardiac vagal modulation in Rheumatoid arthritis and the above mentioned factors may be the consequence of inflammatory process of Rheumatoid arthritis. This finding is well correlated with those published in our previous report 23 …”
Section: Discussionsupporting
confidence: 83%
“…Several other researchers observed similar trends but it was not statistically significant . 9,11,12 Opposite findings were also found in some literature 8,9,11 In this study no significant difference were observed in these parameters when compared between drug naïve and medicated MDD patients. This finding also suggest autonomic dysfunction in MDD patients remained unaffected by treatment with anti depressive drug.…”
Section: Discussionsupporting
confidence: 60%
“…The values of all the spectral parameters in healthy control were almost similar and also with findings, reported by various investigators. [11][12][13] In this study, significantly lower total power, HF power and HF norm and significantly higher LF norm in both drug naive and medicated depressed patients compared to control suggest lower parasympathetic and higher sympathetic drive and higher LH/HF ratio as index of sympathovagal imbalance in MDD patients. Similar observations were also made by some researchers 8,[16][17] .…”
Section: Discussionmentioning
confidence: 93%
“…[10][11][12][13][14][15][16][17][18][19] Different time domain components of HRV has been used as marker of overall cardiac autonomic activity. The task force guideline for HRV analysis have demonstrated the interpretation of these parameters to understand the status, behavior and the balance between sympathetic and parasympathetic function due to their continuous interaction.…”
Section: Discussionmentioning
confidence: 99%